The Implementation of the Inquiry Method in Improving Student Learning Outcomes in the Social Science Subject in Elementary Schools: Classroom Action Research - Wati, Dita Prihatna; Nurwahyuni, Nurwahyuni; Fatayan, Arum (Journal of Education Action Reseach, 2023)
This tudy aims to improve student learning outcomes in the social science subject using the inquiry method in elementary schools. Because student learning outcomes for social studies subjects are still relatively low and can be said to have not reached the minimum score or have not succeeded. Therefore, teachers are required to make changes. In this study, the researchers employed Classroom Action Research (CAR) which consisted of 3 cycles. Furthermore, each cycle had four stages: planning, implementation, observation, and reflection. The subjects of this study were fourth-grade students, totaling 27 people consisting of 14 male students and 13 female students. The tools used to collect data were learning outcome tests, documentation devices, observation sheets, and field notes. The results of this study showed as follows. At the 1st meeting of cycle I, only 5 students (18%) got a score above the Minimum Completeness Criteria. At the 2nd meeting, there was an increase to 7 students (25%). Because it did not meet the criteria for completeness, the researchers then decided to continue to cycle II. At the 1st meeting of this cycle, 9 students (33%) got a score above the Minimum Completeness Criteria. Furthermore, at the 2nd meeting, there was an increase to 10 students (37%). These results were still considered insufficient. Therefore, the researchers continued to cycle III. At the 1st meeting of this cycle, 18 students (66%) got a score above the Minimum Completeness Criteria. Moreover, at the 2nd meeting, it increased to 23 students (85%). In cycle III, the obtained learning outcomes were very good and have reached indicators of success that have been set so that learning completeness has been achieved As a result of this research, learning with the inquiry learning method is a method that can improve Student Learning Outcomes. The application of the inquiry learning method makes the learning process more enjoyable because students can better understand the material clearly. In addition, it can also help students to be more confident and active in developing their potential to show their abilities.